Ecological Restrictions of Spatial Development in Practice of Russian Regions - E. A. Zhalsaraeva; A. V. Shangina; M. A. Dugarzhapova (Вестник Российского экономического университета имени Г. В. Плеханова)
The article describes conditions of spatial development of Russian regions in view of ‘The Strategy of Spatial Development of the Russian Federation up to 2025’ adopted in February 2019. Today the social and economic development of regions has technogeneous character. The anthropogenic impact on nature and climate is increasing, the quality of mineral resources is deteriorating. In this connection ecologic-economic balance becomes an important component of spatial development. The authors provide systematization of factors determining the spatial economic development at the level of regions, including ecological restrictions. During the research they used general academic methods of quantitative and qualitative analysis, scientific abstraction, synthesis and comparison. The current ecologic-economic restrictions for regions with unique natural systems and objects were identified and studied. Focus was made on particularly protected natural territories, which form the basis of ecological framework of regions. Principle groups of factors of spatial development were identified and ecologic-economic restrictions of regional development were described by using two big federal districts – the Republic of Buryatia and the Altay Territory. The authors put forward the lines of spatial development of regional economies with regard to ecological restrictions.